Associations of Paternal Seminal Plasma Metals with their Spouses’ Unexplained Recurrent Spontaneous Abortion (URSA) Risk and the Potential Mediating Role of Oxidative Stress - Hanyan Xi; Rui Yang; Huaqiong Bao; Huiru Li; Youzhu Li; Francis L. Martin; Wei Chen; Liang Chen; Yan Sun; Yan-Yang Lu; Qingyu Huang; Meiping Tian (Biological Trace Element Research, 2025)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Improved PSO-VMD seismic signal denoising method combined with modified wavelet transform - Hui Sun; Hong-yong Ren; Rui Chen; Xing-guo Huang; Wei Zhang; Yan-song Li; Jian Zhang; Yu-bo Yue (Applied Geophysics, 2025)

Opportunities and challenges in the application of Digital Twins for orchard management - Xiaojuan Liu; Leilei He; Shiao Niu; Rui Li; Yaqoob Majeed; Xiaoxu Sun; Jinyong Chen; Xiaojuan Li; Kerry Brian Walsh; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

Overexpression of the cold-repressed StWRKY70 enhances cold-induced sweetening resistance by coordinately attenuating starch-to-sugar conversion and increasing respiratory pathways - Rui Jiang; Chunyan Jiang; Xinyu Ni; Shuting Hu; Xiaoshuang Cui; Danting Li; Hui Sun; Tong Zhou; Jichun Wang; Dianqiu Lv; Xun Liu (Postharvest Biology and Technology, 2025)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

Factors affecting micro(nano)plastic release during intravenous therapy: Direct blood exposure - Haoming Xu; Penghui Li; Yujian Lai; Sujuan Yu; Rui Liu; Guomao Zheng; Bintian Zhang; Qian Sun; Jingfu Liu (Journal of Hazardous Materials, 2025)

A new risk for the recovered Tibetan antelope (Pantholops hodgsonii): Co-exposure of microplastics with organophosphates in their habitats - Rui Guo; Caian He; Jian Sun; Shaohua Li; Chuntao Zhao; Zhiyong Ling; Liang Chen; Wenrui Zhang; Jingmeng Li; Bing Wang; Jufang Hu; Dongmei Yu; et al. (Journal of Hazardous Materials, 2025)

Ureolysis-driven sulfidogenic precipitation and pH enhancement for robust bioremediation of zinc-laden acid mine drainage - Cong Peng; Zhenyu Zhang; Zhendong Yang; Li Zeng; Huijun Xi; Zhenghua Liu; Huaqun Yin; Delong Meng; Yonghong Liu; I.A. Ibrahim; Hongjuan Sun; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2025)

Insights into the combined effect of N2H4 and NH2OH on CANON process in SBR: Nitrogen removal performance, stability of process and microbial community - Zi-Yue Li; Run-Mei Li; Xin Ma; Jia-Min Zhou; Ying-Jun Sun; Xin-Tao Liu; Xin-Rui Zhang; Ying Wang; Zi-Jun Yan; Qian-Qian Zhang; Zai-Yong Zhang (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Phenotypic traits, genetic diversity, and toxigenic potential of Aspergillus flavus from maize ear rots in Sichuan Province, China - Miaomiao Ma; Henan Zhao; Wei Wang; Pan Li; Rui Yang; Jiawen Yang; Cuiping Wu; Xiaofang Sun; Xiaoli Chang; Guoshu Gong (Food Research International, 2025)

Valorization and evaluation of acidic and neutral polysaccharides from Panax ginseng processing residues for the mitigating effects on skin aging - Boyu Xiong; Rui Liu; Xinyi Zhi; Yanru Li; Jiameng Sun; Kaixuan Mao; Lei Yu; Yunfeng Bi (Food Research International, 2025)

Ferritin-alginate oligosaccharide shell core complex for co-encapsulation and synergistic stabilization of astaxanthin and zinc ions - Rui Yang; Jincan Wu; Zexu Li; Yue Li; Chunkai Gu; Xinmei Sha; Li Liang; Shihao Sun; Lei Shi; Yuyu Zhang (Food Hydrocolloids, 2025)

Multi-task deep learning utilizing VOCs detected by HS-GC-IMS for geographical origin tracing and adulteration detection of turmeric powder - Xiao Han; Tong Wu; Shixin Cen; Jie Yong; Xinrang Tian; Xinyi Li; Rui Sun; Minghui Liu; Heshui Yu; Zheng Li (Food Control, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Radial borehole fracturing in the multilayered shale oil reservoir based on a 3D discrete lattice model - Zixiao Xie; Tengda Long; Xiaoguang Wu; Zhongwei Huang; Gensheng Li; Xianzhi Song; Rui Yang; Tao Pan; Wenchao Zou; Zhaowei Sun; Yaoyao Sun; Naikun Hu; et al. (Engineering Geology, 2025)

Unveiling the 3D Li2S nucleation mechanism through ultra-small Ru engineering on MoS2 for high-efficiency Li S batteries - Mengjing Jin; Rui Wang; Shimin Wang; Ru Chen; Jiayue Li; Yanchun Wang; Renqian Tao; Guowen Sun; Jinyuan Zhou; Xiaojun Pan (Chemical Engineering Journal, 2025)

Corrigendum to “Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds” [Chem. Eng. J. Volume 522, 15 October 2025, 166981] - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

Radioactive iodine filled porous networks in self-floating CMPs enabling adsorption-evaporation cooperative decontamination - Rui Jiao; Yiwan Si; Yanju Jing; Jiyan Li; Zhaoqi Zhu; Hanxue Sun; An Li (Chemical Engineering Journal, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

Unveiling the hidden threat: heavy metal accumulation in crops and soil microbial dynamics in a teaching experimental farmland - Xue Gu; Xuegang Yu; Qing Li; Yanjun Mao; Zhiwei Zhou; Huan Hu; Rui Huang; Jiayu Zhou; Yuanyi Sun; Yancheng Li; Aijiang Yang (Plant and Soil, 2025)

Time trend of urine metal levels in preschool children in the electronic waste recycling area and its association with hemoglobin levels - Rongyi Kang; Jieting Chen; Kaihui Li; Rui Sun; Jian Zhang; Chenxu Dai; Xijin Xu; Bo Xie; William W. Au; Lei Tan; Xia Huo (International Archives of Occupational and Environmental Health, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

CFD–DEM and Experimental Investigation of Seepage Behavior at Soil–Structure Interfaces - Xue-min Yang; Zeng-guang Xu; Jun-rui Chai; Cheng Cao; Chao-wei Sun; Gang Li (Geotechnical and Geological Engineering, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Detection of Caco-2 cell absorption rate of Bombyx mori peptide chelated zinc and validation of anti-inflammatory activity based on network pharmacology - Mengqing Guo; Ning Dong; Chunxue Liu; Rui Ma; Shen Li; Yao Sun; Fengqing Zhang (BioMetals, 2025)

Synergistic electromagnetic and chemical enhancements in Al/C3N4/Ag@C for Raman-based chlortetracycline sensing - Jingyi Sun; Lujie Li; Tingting Zhang; Na Jiang; Zishan Guo; Congying Li; Weihua Li; Xianhuai Huang; Yan Li; Rui Lu (Analytica Chimica Acta, 2025)

ZmPOD5 positively regulates drought tolerance by modulating ROS production - Rui Li; Jian Li; Minghao Sun; Yang Qin; Yunling Peng; Yiru Wang; Jun Zheng (Plant Science, 2025)

Unpacking China's land use and trade-driven land transfers through telecoupling - Yaya Song; Xianjin Huang; Qianjing Li; Xinxian Qi; Rui Sun; Mingshu Wang (Land Use Policy, 2025)

A multiscale peridynamic simulation on thermal-mechanical coupling behavior and damage failure mechanism of granite - Heng Li; Sheng-Qi Yang; Rui Yong; Shi-Gui Du; Bo-Wen Sun; Su-Sheng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Influence of fuel side dilution on the combustion characteristics of syngas-air micro-mixing nozzles - Dengke Chen; Penghua Qiu; Chang Liu; Wentong Wang; Rui Sun; Yijun Zhao; Linyao Zhang; Li Liu; Chang Xing (Fuel, 2025)

An intelligent colorimetric paper-based hypoxanthine biosensor enabled by smartphone and dual-enzyme system for efficient shrimp freshness monitoring - Wenhui Dong; Rui Feng; Jiaqi Pang; Kaiyue Wei; Jiao Li; Jianan Sun; Sai Wang; Xiangzhao Mao (Food Chemistry, 2025)

A carrier-assisted strategy for accelerating aerobic granulation under low superficial gas velocity: Critical contributions of sediment biochar and camellia shell biochar carriers - Qingxia Lin; Chuxuan Song; Jun Li; Ziqiang Liu; Xue Hu; Rui Xue; Suiqin Yang; Yang Gao; Wei Zhang; Lean Zhou; Julong Sun; Jinting Wang; et al. (Environmental Research, 2025)

Air pollution, drought, and their synergistic effects on cardiovascular disease risk in China: a nationwide study - Chaohao Ling; Rui Li; Qian Shen; Lulu Cui; Mangen Yang; Zhou Liu; Tianzhao Xu; Wenwen Sun; Shaofu He (Environmental Pollution, 2025)

Aluminum dihydrogen phosphate-melamine modified hollow spheres/epoxy composites: Enhanced flame retardancy, thermal insulation and wave-absorbing properties - Yunxin Ai; Zhaoqi Zhu; Weijun Liu; Hanxue Sun; Jiyan Li; Rui Jiao; An Li (Chemical Engineering Journal, 2025)

Synergistic effects of pore performance and wettability for solar driven evaporation and salt crystallization - Jiyan Li; Tao Zhou; Yongtong Li; Jing Sun; Rui Jiao; Hanxue Sun; An Li (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Gender-specific thermal sensation analysis and SHAP-based prediction across steady, ramp-change, and step-change thermal conditions - Yingle Wei; Jiahua Li; Min Xu; Rui Sun; Fuyuan Xu; Yunsong Han (Building and Environment, 2025)

A block theory-based method for identifying the boundaries and movement modes of potential unstable bodies in rock slopes - Qinkuan Hou; Shuhong Wang; Rui Yong; Zong Li; Wenshuai Han; Wenpan Sun (Rock Mechanics and Rock Engineering, 2025)

Greenhouse Gas Footprints of Maize Cultivation Systems in Different Climate Zones: Field Data Validation and Application of CNMM–DNDC as a Hydro-Biogeochemical Model - Siqi Li; Wei Zhang; Yong Li; Chunyan Liu; Bo Zhu; Job Kihara; Peter Bolo; Zhisheng Yao; Kai Wang; Shenghui Han; Rui Wang; Jiarui Sun; et al. (Advances in Atmospheric Sciences, 2025)

Row-based kiwifruit counting pipeline for smartphone-captured videos using fruit tracking and detection region adaptation guided by support-post - Jiwei Zhang; Liguo Jiang; Leilei He; Zhenchao Wu; Rui Li; Jinyong Chen; Xiaoxu Sun; Yunfei Xue; Anastasia Grecheneva; Spyros Fountas; Longsheng Fu (Computers and Electronics in Agriculture, 2025)

The internal and external reverse-reduction pathway involved in the degradation of free DNA bases during advanced oxidation processes - Shuangshuang Cheng; Rui Cui; Yuehong Sun; Yuxin Li; Yangjian Zhou; Zilong Song; Xin Yang (Water Research, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Crop diversification improves productivity and soil health by regulating fungal diversity - Rui Li; Zhibin He; Peng He; Rong Yang; Dengke Ma; Yuan Li; Yangzhou Xiang; Weihao Sun; Xi Zhu; Zhixin Zhang (Soil and Tillage Research, 2025)

Feasibility of reducing the capacity of plain reservoirs through the joint optimal scheduling of mountain and plain reservoirs - Dingrong Zhai; Aijun Guo; Yimin Wang; Jianxia Chang; Yibin Liang; Zhehao Li; Jingyao Sun; Zhentao Tang; Rui Zheng (Journal of Hydrology, 2025)

Skeleton engineering of conjugated microporous polymer for highly efficient PM capture in harsh environments - Cailin Guo; Wei Liu; Mengxue Li; Peng Mu; Anli Yi; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Journal of Hazardous Materials, 2025)

Long-term variations of global antimony (Sb) deposition fluxes and their responses to China’s clean air actions - Wenwen Sun; Rui Li (Journal of Hazardous Materials, 2025)

Tfh cell-mediated impairment of rotavirus-specific antibodies by PAH and PFAS co-exposure in seropositive children - Jian Zhang; Jieting Chen; Rongyi Kang; Chenxu Dai; Bo Xie; Kaihui Li; Rui Sun; Xiangbin Zheng; Lei Tan; Xijin Xu; Xia Huo (Journal of Hazardous Materials, 2025)

Decoding the spatiotemporal dynamics of cropland carbon emission drivers in China: A machine learning-based analysis - Hanbing Li; Xiaobin Jin; Rongqin Zhao; Bo Han; Xinyuan Liang; Rui Sun (Journal of Cleaner Production, 2025)

A promising strategy for selective recovery of Nb(V) using IRA-410 ion exchange resin: Adsorption performance and mechanism study - Congzhong Tian; Rui Ma; Wenjie Zou; Shifei Sun; Zhengyao Li; Zhijun Zhang; Fang Zhou (Journal of Environmental Chemical Engineering, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Effects of PM2.5 constituents on gestational diabetes mellitus in Chinese pregnant women: The potential modifying role of vitamin B12 - Chen Li; Dongfang Zhang; Xiang Li; Yibin Zhang; Guangbin Sun; Hongyu Zhou; Rui Xi; Haoyang Yuan; Liwen Zhang; Xumei Zhang; Shuying Li; Qiang Zhang; et al. (Environmental Research, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Closing the loop with citramalic acid-based chiral polyester: A novel strategy as a game-changer for sustainable materials - Lei Song; Xinyu Liu; Ruimin Wang; Mo Zhou; Fei Li; Yunlong Sun; Lu Li; Yanming Hu; Ding Zhou; Xiaowei Xu; Mingyuan Zheng; Rui Wang (Chemical Engineering Journal, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Light-confining resonant metamaterial integrated with silicon-doped quantum dots for liquid-phase biomolecular detection - Rui Zhang; Jie Huang; Lanju Liang; Zhuyu Ding; Xin Yan; Guifang Wu; Haiyun Yao; Zhenhua Li; Xiaofei Hu; Ziqun Wang; Zhaoqing Sun (Chemical Engineering Journal, 2025)

Orally administered milk-derived extracellular vesicles alleviate hepatic metabolic dysfunction by targeting hepatocytes and modulating ER stress - Rui Zhang; Haoran Wang; Guoyue Wei; Xipeng Sun; Yifan Zou; Chaoting Wen; Tao Li; Huaxi Yi; Lingjun Tong (Chemical Engineering Journal, 2025)

Multifunctional flexible multilayer pressure sensor for pressure sensing, energy harvesting and versatile applications - Fu-Rui Teng; Song Sun; Si-Chen Tan; Ying-Jie Ma; Yue Huang; Lin Zhu; Di Wu; Ai-Dong Li (Chemical Engineering Journal, 2025)

Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

Selective adsorptive separation of xylene isomers in vapor and liquid phases by nonporous adaptive crystals of leaning pillar[6]arenes - Yu-Xiang Sun; Susu Ren; Gengxin Wu; Xiang-Shuai Li; Haitao Wang; Jia-Rui Wu (Chemical Engineering Journal, 2025)

Interactions and feedback mechanisms in oasis wetland hydrology–soil–vegetation systems, northwestern China - Bing Liu; Ying Zhao; Arash Malekian; Xiao Wang; Wenzhi Zhao; Maliheh Behrang Manesh; Bin Wang; Changkun Yang; Weihao Sun; Wen Li; Pouyan Dehghan Rahimabadi; Yangyang Meng; et al. (CATENA, 2025)

Efficacy Evaluation of Selenium-enriched Akkermansia muciniphila in the Treatment of Colon Tumor Mice - Xiaoqian Li; Wen Rui; Pingting Shu; Yuhang Sun; Jingpeng Yang (Probiotics and Antimicrobial Proteins, 2025)

Sinomenine enhances recovery from corneal alkali burns by attenuating macrophage M1 polarization through modulating the METTL3/IRAKM axis - Jun-qi Li; Rui-ze Sun (Journal of Molecular Histology, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

Emerging MXene-based Composites: Synthesis, and Recent Advances in Food Contaminant Analysis - Mengmeng Gao; Rongchao Li; Huilin Li; Xiaochun Hu; Jingming Sun; Hao Wang; Rui Gao; Huilin Liu; Mingfei Pan; Shuo Wang (Trends in Food Science & Technology, 2025)

The impact of wave-induced mixing on the simulation of the upper mixed layer in climate models - Yujie Jing; Jian Sun; Rui Li; Kejian Wu; Zipeng Yu; Pengfei Lin; Xianghui Dong; Alexander V. Babanin (Ocean Modelling, 2025)

Sub-soil biodegradable film mulching: A sustainable solution for enhancing winter wheat yield and shaping soil microbial communities in saline-alkali soils - Changyuan Wang; Junwei Dong; Boxiang Ji; Yahui Lv; Yixuan Song; Quanqi Li; Chitao Sun; Rui Zong; Mingming Zhang (Journal of Hazardous Materials, 2025)

Reconstructing the tectonic evolution of the Mudanjiang Ocean: Metamorphic insights from the Heilongjiang Complex, NE China - Guang-Ming Sun; Xu-Ping Li; Hans-Peter Schertl; Jin-Rui Zhang; Xiao Wang; Wen-Yong Duan (Journal of Asian Earth Sciences, 2025)

Deep-sea rare earth element-rich sediments: A review of distribution, carriers and petrogenesis - Yu Fu; Zhengkun Li; David Chew; Pete Hollings; Jinzhou Peng; Jieyun Chen; Bojue Tan; Gaowen He; Yongjia Liang; Fei Huang; Yayue Tang; Rui Wang; et al. (Global and Planetary Change, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Protective effects of rosmarinic acid against oxidative damage and atherosclerosis via the PI3K/AKT pathway - Tiantian Tang; Mingze Sun; Baiyuan Sha; Rui Liu; Zhiyang Ren; Liwei Li; Ye Zhang; Hao Wang; Kai Yu (Food and Chemical Toxicology, 2025)

Template synthesized spider network-like conjugated microporous polymers composite membranes with high mechanical properties for separation and flexible wearable devices - Yong Zhang; Wenwen Luo; Zhentao Hu; Hanxue Sun; Zhaoqi Zhu; Jiyan Li; Rui Jiao; An Li (Chemical Engineering Journal, 2025)

Performance-differentiated phase change sandwich composite with gradient thermal conductivity for transient thermal shock protection and multi-source thermal management - Zihan Wang; Xinze Li; Chenbo He; Rui Yang; Mingyang Yang; Guihua Tang; Hu Zhang; Qi Xie; Jingjing Sun; Chencheng Sun; Junning Li (Chemical Engineering Journal, 2025)

Novel microbial fuel cell integrating anoxic/oxic-membrane bioreactor design for simultaneous energy recovery and carbon–nitrogen removal from shale oil and gas wastewater - Simin Zhou; Guangzhi Wang; Likun Huang; Shaofang Li; Chaopeng Li; Rui Zhao; Xiyu Sun; Dongdong Wang (Bioresource Technology, 2025)

Root-soil-microbe interactions mediate phosphorus and iron uptake from lithium iron phosphate nanomaterials - Yaqi Jiang; Yi Sun; Changcheng An; Pingfan Zhou; Yuanbo Li; Quanlong Wang; Jason C. White; Yukui Rui; Peng Zhang (Applied Soil Ecology, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

Global impact of fire emission on ambient nitrate (NO3-) and health effects during 2005–2019 - Wenwen Sun; Dongmei Tang; Rui Li (Journal of Hazardous Materials, 2025)

Structural characteristics of two polysaccharides from L. fumosum (Pers.) P.D. Orton. and their immunomodulatory effects on RAW264.7 macrophages - Rui-Fang Zhong; Wen-Lin Sun; Yi-Meng Li; Jian Chen (Food Research International, 2025)

Identification of potential natural compounds to relieve deoxynivalenol-induced intestinal damage based on bioinformatics and reverse network pharmacology - Rui Li; Kang Feng; Yu Du; Xuebin Fan; Yaqin Zhang; Chenli Wang; Jingdi Zhang; Sheraz Ahmad; Rafique Amna; Ci Liu; Ruiyan Niu; Zilong Sun (Food and Chemical Toxicology, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Ferrocene enhanced interface coupling between Co-MOF and Co nanoparticle for efficient electrocatalytic oxygen reduction - Qin Li; Jinghan Sun; Aiguo Kong; Rui Liu (Chemical Engineering Journal, 2025)

Corrigendum to “Surface segregation on Ag@MNi (M = Pd, Pt, Rh, and Ru) core–shell nanocrystals for enhancing the oxygen reduction performance” [Chem. Eng. J. 500 (2024) 156765] - Xinyuan Zhou; Qiyan Sun; Xinlin Wang; Ruixue Zhang; Bin Li; Zexing Wu; Dehong Chen; Lei Wang; Guang-Rui Xu (Chemical Engineering Journal, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Precursor ratio-modulated enzyme-mimicking ZIF-67 nanoflower array: A colorimetric “electronic tongue” for antioxidant monitoring - Peitong Yu; Boxu Wang; Huikai Lin; Weirong Zhou; Jiaxiong Li; Geyu Lu; Chunyan Sun; Rui Jin (Chemical Engineering Journal, 2025)

Iron valence regulates sulfur pollution in livestock manure compost: A multipath strategy of chemical fixation-oxidation and microbial metabolism - Qi Wu; Wenfang Gao; Xu Wang; Rui Sun; Yanjie Jiao; Xiang Li; Zimin Wei (Chemical Engineering Journal, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Listwise ranking predictor for evolutionary neural architecture search - Nan Li; Lianbo Ma; Rui Wang; Shi Cheng; Yanan Sun; Bing Xue; Mengjie Zhang (Swarm and Evolutionary Computation, 2025)

Improving agricultural mulching to reduce environmental footprint and enhance economic profit across China - Huihui Wei; Yifan Yang; Li Zhang; Zutao Ouyang; Matthew Tom Harrison; Ke Liu; Guojun Sun; Gary Y. Gan; Feng-Min Li; Li Dong; Rui Wang; Bo Wang; et al. (Resources, Conservation and Recycling, 2025)

Sesquiterpenoids isolated from the root bark of Lycium chinense - Xiao-xia Wang; Qian Liu; Ning Wang; Rui-li Zhang; Xiao Li; Peng-yu Zhuang; Hang Liu; Liang-dan Sun; Yang Jin (Phytochemistry, 2025)

Alterations in microbial-mediated methane, nitrogen, sulfur, and phosphorus cycling within paddy soil induced by integrated rice-fish farming - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Sun Wei; Bing Li; Jian Zhu (Journal of Environmental Management, 2025)

Effects of organic acids on the physico-chemical and functional characteristics of mung bean globulin amyloid fibrils - Peng Jiang; Shu Zhang; Tianxin Fu; Jingru Sun; Rui Ma; Xuejian Song; Jingjing Diao; Zhijiang Li; Changyuan Wang (Food Bioscience, 2025)

Development of recyclable polyvinyl alcohol-based transparent films with enhanced UV shielding for sustainable fruit preservation packaging - Xiaoli Liu; Tianyu Sun; Xiaoqing Wang; Rui Huang; Xuanxuan Huang; Xin Li; Zhanhui Lu (Food Packaging and Shelf Life, 2025)

3D geological modeling of tunnel alignment in the complex mountainous region of Yongshan, China, based on multisource data fusion - Huaiyuan Sun; Liuyang Sheng; Yiming Dai; Xiaojun Li; Yi Rui; Linhai Lu (Engineering Geology, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Influence of meteorological variables and human activities on precipitation chemistry in the Guanzhong Plain, Northwest China - Rui Sun; Xiaofei Li; Huayu Huang; Chi Zhou; Yibo Wang (Atmospheric Pollution Research, 2025)

Synergistic effect of canine FGF-21 combined with insulin in the treatment of canine diabetes - Wenying Sun; Yaoqun Wang; Ziran Liu; Qing Wu; Xiaochen Guo; Zhitong Li; Xinyu Li; Chunxu Shi; Rui Gao; Lin Bai; Jingming Wang; Yuhan Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Associations Between Metal–Metal Interaction and the Risk of Hypertension: A Case–Control Study in Chinese Community-Dwelling Elderly - Meiyan Li; Yihong Di; Siyu Duan; Rui Wang; Pei He; Zhongyuan Zhang; Yuqing Dai; Zhuoheng Shen; Yue Chen; Huifang Yang; Xiaoyu Li; Jian Sun; et al. (Cardiovascular Toxicology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

An integrated colorimetric biosensing platform containing microneedle patches and aptasensor for histamine monitoring in seafood - Wenjing Wang; Rui Feng; Kaiyue Wei; Jiashuo Xu; Wenhui Dong; Jiao Li; Jianan Sun; Sai Wang; Xiangzhao Mao (Journal of Hazardous Materials, 2025)

Microbial characteristics accompanied with electricity generation in response to the polyaniline derived covalent organic framework-carbon nanotube composite modified sludge microbial fuel cell - Fengfei Sun; Ziren Sun; Rui Li; Yuewei Yang; Meizhen Tang; Junfeng Chen (Journal of Environmental Chemical Engineering, 2025)

Simultaneous ammonium recovery and organic removal from domestic wastewater in a stacked bipolar membrane electrodialysis reactor coupled with membrane contactor (BMED-MC) - Yueting Wu; Lulu Qin; Longjing Sun; Rui Shu; Dan Sun; Hua Li; Xue Xia (Journal of Environmental Chemical Engineering, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Enhanced Cr(VI) adsorption by DOM-coated iron-manganese binary oxides: Process and mechanisms - Zeyu Zhang; Xiaole Ti; Rui Yang; Yuxi Tang; Beidou Xi; Xiaojie Sun; Wenjie Zhang; Ningjie Li (Journal of Environmental Chemical Engineering, 2025)

Fluorescent molecularly imprinted hydrogel sensing strip based on nitrogen-doped carbon dots and inverse opal photonic crystals applying for effective detection for imidacloprid in fruits and vegetables - Mingfei Pan; Mengmeng Gao; Jingjing Cui; Rui Gao; Huilin Li; Jingming Sun; Wenjie Chen; Shuo Wang (Food Chemistry, 2025)

Development of aroma attributes and volatile components during liquid-state fermentation of instant dark tea by Aspergillus niger - Haoran Sun; Yaling Cao; Rui Fang; Jia Li; Shanshan Shen; Shengshuo Zhang; Ranqin Fan; Jialin Fu; Feng Zou; Pengxiang Yue; Yu Wang; Xueling Gao (Food Bioscience, 2025)

A miRNA-mRNA study reveals the reason for quality heterogeneity caused by marbling in triploid rainbow trout (Oncorhynchus mykiss) fillets - Falie Shi; Qianwen Li; Guoliang Sun; Fulei Wei; Zezhong Wu; Yuqiong Meng; Rui Ma (Food Bioscience, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

Global landscape fire-sourced ambient benzene and health risks in different future scenarios - Wenwen Sun; Dongmei Tang; Yuanzhi Yao; Rui Li (Environmental Pollution, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Antimicrobial Peptides: Classification, Mechanism, and Application in Plant Disease Resistance - Yuan-Zhen Wu; Jin Wang; Ying-Hui Hu; Qi-Shuo Sun; Rui Geng; Li-Na Ding (Probiotics and Antimicrobial Proteins, 2025)

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Ginsenoside Rf in wild ginseng adventitious roots extract inhibits melanogenesis via cAMP/PKA and NO/cGMP signalling pathways in α-melanocyte-stimulating hormone-stimulated B16F10 mouse melanoma cells and zebrafish - Hong Chen; Mengqiong Jian; Huanhuan Teng; Zhenzhuo Li; Xiaohao Xu; Xiangzhu Li; Rui Jiang; Daqing Zhao; Liwei Sun; Jianzeng Liu (Natural Product Research, 2025)

Metabolic response and adaption to chronic hypoxia of triploid rainbow trout by the crosstalk between the liver and muscle - Lu Bai; Guoliang Sun; Jiao Li; Jun Sun; Zezhong Wu; Changzhong Li; Rui Ma; Yuqiong Meng (Aquaculture, 2025)

Macrofaunal biodiversity and trophic structure varied in response to changing environmental properties along the Spartina alterniflora invasion stages - Li Yang; Rui Pan; Shuang Wang; Zhangyan Zhu; Hongshan Li; Ruiping Yang; Xiaoping Sun; Baoming Ge (Marine Pollution Bulletin, 2025)

Tracking of single virus: Dual fluorescent labeling of pseudorabies virus for observing entry and replication in the N2a cells - Mingzhi Li; Li Pan; Caoyuan Ma; Hongxia Wu; Guangtao Xiang; Lian-Feng Li; Tao Wang; Rui Luo; Yongfeng Li; Di Liu; Huanjie Zhai; Moon Assad; et al. (Veterinary Microbiology, 2025)

The Quanjishan Charnia assemblage from the northern Qaidam Basin, Tibetan Plateau, and implications for palaeoecology and taphonomy of Ediacaran fronds - Chengxi Wu; Alexander G. Liu; Yarong Liu; Xiaopeng Wang; Guangjin Li; Hanzhi Qu; Rui Huang; Mingyang Qiu; Wentao Zheng; Yunpeng Sun; Hongyi Shi; Qing Ouyang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A density-point network for dense tiny stored grain pest counting - Runsheng Qi; Rui Li; Jie Zhang; Yi Xia; Jianming Du; Jiahui Sun; Long chen; Chengjun Xie; Hui Zhang; Guangyu Li (Journal of Stored Products Research, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Fabrication of CMC-PVA-EGDE hydrogels for maintaining overall postharvest quality of small-size packaged straw mushroom - Rui Jin; Xin-Lin Li; Wei Jia; Wen Li; Lei Sun; Yan Yang; Jing-Song Zhang; Wen-Jing Sun; Feng-Jie Cui (Food Chemistry, 2025)

Design of an injectable magnetic hydrogel with porous structure and electrocatalytic activity for the sensitive electrochemical detection of nitrite in foods - Yongfeng Chen; Shixin Li; Rui Gao; Yujie Shi; Yufeng Sun; Geoffrey I.N. Waterhouse; Zhixiang Xu (Food Chemistry, 2025)

In-field degradation of polybutylene adipate-co-terephthalate (PBAT) films, microplastic formation, and impacts on soil health - Kai Wang; Markus Flury; Shiyan Sun; Junling Cai; Aihua Zhang; Qiang Li; Rui Jiang (Environmental Research, 2025)

Integrated rice-fish farming dynamically altered the metal resistances and microbial-mediated iron, arsenic, and mercury biotransformation in paddy soil - Yiran Hou; Rui Jia; Linjun Zhou; Liqiang Zhang; Wei Sun; Bing Li; Jian Zhu (Environmental Pollution, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

In-situ preparation of CMPs based electrospun nanofibrous composite membranes for effective air filtration and oil–water separation - Yong Zhang; Anli Yi; Yongtao Ren; Cheng Niu; Jian Jiang; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Chemical Engineering Journal, 2025)

Doping-engineered regulation of Co(IV)=O enhanced Fenton-like activities via electronic structure modulation on CoSCN nanotubes - Liang Ge; Jian Wei; Junyong He; Rui Sun; Wenlong Wang; Dandan Yang; Jiandong Lu; Peidong Hong; Yulian Li; Yahui Li; Chao Xie; Zijian Wu; et al. (Chemical Engineering Journal, 2025)

Superior matching between electrochemical and non-electrochemical reactions to boost furfural electro-oxidation - Jianyuan Deng; Rui Li; Kun Xiang; Longzhou Zhang; Kaihang Sun; Young Dok Kim; Zhongyi Liu; Jingmin Ge; Zhikun Peng (Chemical Engineering Journal, 2025)

Impact of long-term drip irrigation on soil organic carbon and nutrient stocks in arid oasis farmlands - Weihao Sun; Zhibin He; Bing Liu; Dengke Ma; Rui Li; Shuai Wang; Arash Malekian (CATENA, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Formation design for interplanetary shock imaging interferometric array - Yuan Wang; Li Deng; Jingye Yan; Rui Li; Xiucong Sun; Tianshan Dong; Shenggang Liu (Advances in Space Research, 2025)

Digitalization and sustainable development: How could digital economy drive circular economy development in China? - Yingshan Sun; Rui Zhang; Xiaotong Qie; Dongxue Li; Xiaoyi Zhang; Xiaolu Du; Yue Wang (Environment, Development and Sustainability, 2025)

Cu-EAB zeolite catalyst: A promising candidate with excellent SO2 poisoning resistance for NH3-SCR reaction - Xiangqiong Jiang; Yu Sun; Rui Li; Dongdong Chen; Yuyan Yao; Zhifeng Zeng; Can Yang; Hongwei Chen; Hongzheng Chang; Yulong Shan; Carmine D’Agostino; Jiuxing Jiang (Journal of Hazardous Materials, 2025)

Purification of solid waste phosphogypsum by various cationic collectors: Experimental study and theoretical calculation - Kaizhen Wu; Rui Li; Xuchao Sun; Fang Shen; Lutao Xue; Shiping Zhang; Xiaoyong Wu; Yubiao Li; Ruan Chi (Journal of Environmental Management, 2025)

Solar interfacial evaporator based on robust aligned channels bacterial cellulose aerogels for wastewater treatment - Jiyan Li; Min Qiao; Shuo Gao; Tao Zhou; Rui Jiao; Fei Wang; Hanxue Sun; An Li (Journal of Environmental Chemical Engineering, 2025)

Carboxymethyl chitosan/oxidized hyaluronic acid hydrogel-encapsulated hucMSC-derived exosomes for enhanced hepatic regeneration and post-hepatectomy applications - Qiuxia Zheng; Jia Yao; Zongbin Sun; Rui Li; Yue Zhang; Pan Jiang; Ye Xie; Xiaojing Song; Hongfa Sun; Dan Zhu; Haixu Ni; Xun Li (Carbohydrate Polymers, 2025)

High-throughput screening method for glycolipids based on substrate modification and their efficient biomanufacturing - Yuanyi Li; Zhilin Liu; Yiming Zheng; Ke Sun; Peng Lei; Yian Gu; Yongting Song; Jian Xue; Weidong Cai; Rui Wang; Hong Xu; Liang Sun (Bioresource Technology, 2025)

Gut microbiota’s role in high-altitude cognitive impairment: the therapeutic potential of Clostridium sp. supplementation - Wei Zhou; Yongqiang Zhou; Shikun Zhang; Bin Li; Zhong Li; Zhijie Bai; Dezhi Sun; Chaoji Huangfu; Ningning Wang; Tiantian Xia; Congshu Huang; Lina Guan; et al. (Science China Life Sciences, 2025)

Characterization and Assessment of Sheep-Origin Probiotic Bacillus licheniformis B63 Strain for Potential Use in Intestinal Health and Disease - Meng Hou; Yabin Lu; Mengjun Ye; Na Li; Yawei Sun; Gang Yao; Jinquan Wang; Fangfang Yin; Qimin Peng; Sheng Jia; Rui Shi; Xuxiang Wang (Probiotics and Antimicrobial Proteins, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Paeoniflorin-mediated downregulation of VEGFA: unveiling the therapeutic mechanism of buyang huanwu decoction in diabetic retinopathy - Wentao Sun; Rui Wang; Ke Gong; Liping Wang; Fengzhi Li; Jin Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Reconstruction of well-logging data using unsupervised machine learning-based outlier detection techniques (UML-ODTs) under adverse drilling conditions - Jing-Rui Chen; Rui-Zhao Yang; Ting-Ting Li; Yun-Di Xu; Zhi-Peng Sun (Applied Geophysics, 2025)

An amino-functionalized magnetic mesoporous silica nano-adsorbent for removing antibiotics from aqueous environments - Sihai Hu; Liuyan Tang; Rui Zhang; Ran Sun; Yuchen Zhang; Zhengcang Song; Yasong Li; Yaoguo Wu; Xujiang Chao; Yuezhou Zhang (Journal of Water Process Engineering, 2025)

A fluorescent aptasensor for deoxynivalenol detection based on Nb.BbvCI-assisted targeted-responsive three-way junctions integrated DNA walking machine - Kai Wang; Xiaohai Yan; Jiamin Wu; Jianrui Qi; Mengge Ning; Menghui Li; Rui Sun; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Chemistry, 2025)

A rapid and nondestructive quantitative detection method for total and organic selenium in selenium-enriched kefir grain based on hyperspectral imaging - Menghui Li; Jinyi Yang; Xing Guo; Rui Sun; Gechao Zhang; Wenhui Liu; Yuanye Liu; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Control, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

Distribution and ecological risks of microplastics in a tropical tourism island area in Hainan, China - Weijie Bian; Rui Sun; Yurui Li; Shuguo Lü; Dongwei Yang; Hongbo Li; Yingxu Zeng; Min Liu (Journal of Oceanology and Limnology, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

Groundwater environmental effects risk evaluation in mountain tunnel construction: A dynamic decision support system based on fuzzy two-dimensional cloud probability model - Huaiyuan Sun; Ling Le; Yiming Dai; Yi Rui; Hehua Zhu; Xiaojun Li; Xuhui Li; Guangwen Xue (Tunnelling and Underground Space Technology, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Efficient removal of cationic malachite green using co-pyrolyzed corn straw biochar-montmorillonite composites - Xiaodong Yang; Zhiyong Hou; Xuefei Yang; Minghui Li; Yuanxia Guo; Kai Wang; Shuaiqi Luo; Jin Zhao; Pengkai Sun; Qiang Yang; Rui Chen; Yan Yan; et al. (Journal of Environmental Management, 2025)

Precise and panoramic study on the nutritional components of specific milk of goats and sheep - Xiaowei Wang; Qian Li; Qiu Zhang; Yanzhi Wu; Rui Chen; Yinggang Sun; Yuan Pan; Siyi Li; Zeying Wang (Food Chemistry, 2025)

Preparation strategy of molecularly imprinted polymers adsorbent based on multifunctional carrier for precise identification and enrichment of fenthion - Lingjun Geng; Jingjing Liu; Jingcheng Huang; Haifang Wang; Peisen Li; Rui Xu; Chengqiang Li; Haowei Dong; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

UPLC-HDMS revealed numerous novel compounds in soybean crude oil - Zhaohui Sun; Feng Dong; Rui Zhang; Xinyu Song; Xiaocai Huang; Yingran Dong; Xiaofei Jia; Shunian Luo; Ying Li; Maoqing Wang (Food Chemistry, 2025)

Novel time-resolved fluorescent-based multiplex immunochromatography test strip for simultaneous detection of pesticides in vegetables - Zhengtao Li; Haowei Dong; Haifang Wang; Donghan Li; Shuxian Zhou; Shengxi Zhai; Jingcheng Huang; Rui Xu; Wenping Zhao; Mohamed Bedair M. Ahmed; Gili Bisker; Xia Sun; et al. (Food Chemistry, 2025)

ACE inhibitory effect and saltiness-enhancing properties of chicken-derived umami peptides: Digestive stability, inhibition kinetics, multiple ligand docking and central composite design - Haotong Zhang; Li Liang; Baoguo Sun; Rui Yang; Zunying Liu; Xiangzhao Mao; Yuyu Zhang (Food Chemistry, 2025)

The responses of root exudates and microbiome in the rhizosphere of main plant and aromatic intercrops to soil Cr stress - Rui Li; Zhenglin Li; Kui Zhang; Cong Zhang; Yue Sun; Jie Zhang; Yi Zheng; Yuncong Yao; Xiaoxiao Qin (Environmental Pollution, 2025)

Revealing the blocking effect of hemicellulose on the formation of closed pores in reed-derived hard carbon for sodium-ion batteries - Zhouhao Fu; Dan Jiang; Zheng Tang; Zhi Tang; Jia Zhou; Rui Liu; Huanhuan Li; Dan Sun; Yougen Tang; Haiyan Wang (Chemical Engineering Journal, 2025)

Transcriptome Analysis Reveals the lncRNA-mRNA Co-expression Network Regulating the Aestivation of Sea Cucumber - Xiaomei Chen; Wentao Han; Rui Yang; Xuan Zhu; Shengwen Li; Yangfan Wang; Xue Sun; Yuli Li; Lisui Bao; Lingling Zhang; Shi Wang; Jing Wang (Marine Biotechnology, 2025)

Associations of phthalate and phthalate alternative metabolites in urine with the risk of gallstones in adults: a cross-sectional analysis - Tianshan Shi; Di Li; Donghua Li; Peng Xie; Jin Sun; Tingrong Wang; Rui Li; Zixuan Zou; Zhenjuan Li; Xiaowei Ren (Environmental Geochemistry and Health, 2025)

An efficient, high-throughput enrichment system for the rapid detection of E. coli at low concentrations in water - Binghuan He; Fangzhou Zhang; Pengfei Gong; Rui Sun; Jianxin Cheng; Chenghui Jin; Bo Liu; Jianlong Zhao; Shilun Feng; Bei Li (Analytica Chimica Acta, 2025)

Spatiotemporal estimates and health risks of atmospheric trace metals across Hong Kong during 2016–2020 - Wenwen Sun; Shenghua Zhang; Dongmei Cai; Liqiang Wang; Ji Jin; Rui Li; Zhenghu Chen (Air Quality, Atmosphere & Health, 2025)

Antibacterial Effect and Network Pharmacology Mechanism of Male Bombyx mori. on Escherichia Coli - Mengqing Guo; Ning Dong; Chunxue Liu; Rui Ma; Shen Li; Yao Sun (International Journal of Peptide Research and Therapeutics, 2025)

Ultralight aerogels with aligned channels for efficient solar driven interfacial evaporation of brackish water and remediation of saline soils - Min Qiao; Jiyan Li; Shuo Gao; Tao Zhou; Rui Jiao; Hanxue Sun; An Li (Journal of Water Process Engineering, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Human settlement and destructive activities disrupt the positive contribution of dust to plant biomass growth over the past 2000 years - Lin Chen; Youliang Huang; Menghan Qiu; Zhilun Li; Rui Yang; Mengjing Li; Huiling Sun; Lixiong Xiang; Shanjia Zhang; Xiaozhong Huang; Aifeng Zhou (Global and Planetary Change, 2025)

A prediction model of the optimal defrosting initiating time for the air source heat pumps with different configurations and operations - Shiquan Wang; Wenzhe Wei; Jianfei Luo; Wei Wang; Yuying Sun; Zhaoyang Li; Chengyang Huang; Rui Tang; Shiming Deng (Energy and Buildings, 2025)

Encapsulation of phase change materials in conjugated microporous polymers hollow microspheres for continuous solar-driven seawater desalination - Yanju Jing; Yong Long; Yiwan Si; Jiyan Li; Hanxue Sun; Rui Jiao; Zhaoqi Zhu; Weidong Liang; An Li (Chemical Engineering Journal, 2025)

Reversible multilevel stimuli-responsiveness and multicolor room temperature phosphorescence to fluorescence transition based on a metal–organic framework system - Hui-Li Sun; Zhong-Hao Wang; Rui-Qi Huang; Zhuo-Di Chen; Mei Pan (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Enhancement of thermal conductivity of graphene-based phase change composites by alternating positive and negative pressures during perfusion - Ruichuan Li; Xianxian Sun; Rui Zhang; Shasha Wang; Qiqi Liu; Peijia Bai; Ye Yuan; Yibin Li (Chemical Engineering Journal, 2025)

Highly active and CO-resistant PdRuMo/C with a wide potential-stable window toward alkaline hydrogen oxidation reaction - Chunxiao Chai; Haoliang Huang; Hao Yang; Jiaqi Qin; Chongyun Sun; Yongpeng Li; Zhaoqi Wang; Xinwei Zhao; Zhongyu Qiu; Tiantian Li; Jiahuan Li; Rui Gao; et al. (Chemical Engineering Journal, 2025)

ε-Poly-L-lysine/rhamnolipid bifunctional coating based on green electrostatic assembly technology for fruit packaging and preservation - Quanfei Li; Qian Chen; Kai Yang; Hao Liu; Delei Xu; Yian Gu; Liang Sun; Peng Lei; Rui Wang; Hong Xu (Chemical Engineering Journal, 2025)

In-situ constructing 3D nanocarbon conduction conformal network on silicon anodes for high-performance sulfide-based all-solid-state batteries - Rui Huang; Ruilong Li; Shaobo Li; Wen Yang; Yu Bai; Zhenhua Wang; Kening Sun (Chemical Engineering Journal, 2025)

Precipitation events and long-term nitrogen addition synergistically stimulate heterotrophic respiration in a semi-arid meadow steppe - Tianhang Zhao; Xu Yang; Rui He; Junqin Li; Wenzheng Song; Yanan Li; Baoku Shi; Weifeng Gao; Wei Sun (CATENA, 2025)

Development of chromosome-specific potential intron polymorphism markers in watermelon - Liang-Jie Li; Ding-Ding Zuo; Meng-Ling Zheng; Lu Yang; Rui Sun; Xue‑Jie Zhu; Zhong‑Hou Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)